Do accountability and voucher threats improve low-performing schools? - Figlio, David N.; Rouse, Cecilia Elena (National Bureau of Economic Research, 2005)
"In this paper we study the effects of the threat of school vouchers and school stigma in Florida on the performance of "low-performing" schools using student-level data from a subset of districts. Estimates of the change in school-level high-stakes test scores from the first year of the reform are consistent with the early results used by the state of Florida to claim large-scale improvements associated with the threat of voucher assignment. However, we also find that much of this estimated effect may be due to other factors. While we estimate a small relative improvement in reading scores on the high-stakes test for voucher-threatened/stigmatized schools, we estimate a much smaller relative improvement on a lower-stakes, nationally norm-referenced, test. Further, the relative gains in reading scores are explained largely by changing student characteristics. We find more evidence for a positive differential effect on math test scores on both the low- and highstakes tests, however, the results from the lower-stakes test appear primarily limited to students in the high-stakes grade. Finally, we find some evidence that the relative improvements following the introduction of the A Plan by low-performing schools were more due to the stigma of receiving the low grade rather than the threat of vouchers"--National Bureau of Economic Research web site.
Keywords: Educational vouchers -- Florida; School improvement programs -- Florida